KUALITAS ELIT DESA PADA PEMILIHAN KEPALA DESA SERENTAK DI DESA NGASO KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2016 - Rity Anggara; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The three candidates for the 2016 Rokan Hulu District Head of Ngaso Kacamatan Ujung Batu Village Election were figures who were once the elite of Ngaso Village Ujung Batu District, Rokan Hulu Regency, namely having been an adat administrator, village head, and Chair of the Ngaso Kecamatan Village Consultative Body (BPD) Ujung Batu Rokan Hulu Regency. Formulation of the problem in the study: how is the quality of the village elite in the simultaneous village head election in Ngaso Village Ujung Batu District, Rokan Hulu Regency in 2016 ?, and what factors are the strengths and weaknesses of each village elite in the simultaneous election of village heads in Kecamatan Ngaso Village Ujung Batu in Rokan Hulu Regency in 2016? The objective of the study was to determine the quality of village elites in the simultaneous village head elections in Ngaso Village Ujung Batu District, Rokan Hulu District in 2016, and to find out which factors were the strengths and weaknesses of the elite in the simultaneous election of village heads in Ngaso Village Ujung Batu District, Rokan Hulu District 2016. Source of primary data through interviews and secondary data sources. Data analysis techniques were carried out with qualitative descriptive analysis. Instrumental quality, each participant has managerial competence as an advantage, Andes Siata has the advantage of functional competence in the economic field compared to 2 (two) other candidates. The symbolic dimension, the basic principles of each candidate are active in every social activity, while the emotional aura of the three candidates has an ambitious, upbeat and optimistic spirit, which is a differentiator is the humorous nature possessed by the Andes Siata more, the inspirational aura of Siata Andes more compared to the other two figures, the community considers Andes Siata to be a hard-working person so that his business has grown rapidly, Andes Siata's social aura represents himself as a successful businessman, Busri has a social aura as an experienced person in government, and Engki Mula Putra is representation of young people and people who have experience in government. Optical phenotype, the physical charm of the three candidates has a body that is obese or not athletic, and a face that is considered ugly is not bad and is said to be handsome or not handsome or not artistically, health and fitness are always energetic and active despite having a fat body. The style of appearance shown by the candidate is neat and polite. Keywords: quality, village elite, village head election